Method and device for condition monitoring - Bernhard Randerath and Mike Gerdes and Dieter Scholz (2012)
A computer-implemented method, a computer program product and a device for the condition monitoring of a component or system, such as for an aircraft or spacecraft. The method includes: providing an optimized decision tree, the nodes of which contain attributes of an input vector, the leaves of which each contain a classification function and the connections of which between the nodes are weighted; providing an input vector derived from a data signal; implementing a condition monitoring in which the condition of the component or system is determined using the weighted decision tree and on the basis of the input vector. In addition to an item of information concerning which of the classification functions of the decision tree best corresponds to the input vector, an additional item of information concerning the probability with which the other classes of the decision tree correspond to the examined input vector is calculated and output.
Keywords: aircraft; spacecraft; test; inspection; condition monitoring; decision tree; classification function